2016
DOI: 10.1371/journal.pbio.1002515
|View full text |Cite
|
Sign up to set email alerts
|

Topological Small-World Organization of the Fibroblastic Reticular Cell Network Determines Lymph Node Functionality

Abstract: Fibroblastic reticular cells (FRCs) form the cellular scaffold of lymph nodes (LNs) and establish distinct microenvironmental niches to provide key molecules that drive innate and adaptive immune responses and control immune regulatory processes. Here, we have used a graph theory-based systems biology approach to determine topological properties and robustness of the LN FRC network in mice. We found that the FRC network exhibits an imprinted small-world topology that is fully regenerated within 4 wk after comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
190
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(205 citation statements)
references
References 64 publications
(92 reference statements)
12
190
3
Order By: Relevance
“…These predictions warrant further experimental analysis. In addition, a more detailed analysis of our artificially generated FRC network showed that this network has a similar mean shortest path length to a random network but a much greater degree of clustering giving a large small-worldness value indicative of a small-world type network, which is qualitatively but not quantitatively matching to what was found experimentally [14]. In our study, we were interested in assessing the small-worldness property of the model network graph embedded into metric space, i.e.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…These predictions warrant further experimental analysis. In addition, a more detailed analysis of our artificially generated FRC network showed that this network has a similar mean shortest path length to a random network but a much greater degree of clustering giving a large small-worldness value indicative of a small-world type network, which is qualitatively but not quantitatively matching to what was found experimentally [14]. In our study, we were interested in assessing the small-worldness property of the model network graph embedded into metric space, i.e.…”
Section: Discussionmentioning
confidence: 54%
“…The values suggest that this network has a similar mean shortest path length to a random network but a much greater degree of clustering giving a large small-worldness value indicative of a small-world type network. Analysis of actual FRC networks have shown average small-worldness values of 6.128 across 6 mice [14]. This is of particular relevance to FRC networks given their hypothesised role in maintaining chemokine gradients.…”
Section: Graph Measuresmentioning
confidence: 79%
See 3 more Smart Citations